Governance, social stability, and unionism in Nigeria: An analysis of the Buhari and Tinubu administrations (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This paper reconnoiters governance, social stability, and unionism in Nigeria, with a focus on the administrations of Presidents Muhammadu Buhari and Bola Ahmed Tinubu. It scrutinizes the socio-political challenges that have molded Nigeria’s governance, including political instability, economic oscillations, and security crises, heightened by historical legacies of colonialism and military rule. Labor unions, chiefly the Nigeria Labour Congress (NLC) and the Trade Union Congress (TUC), have played a crucial role in influencing government policies and sustaining social discourse. Both Buhari and Tinubu faced strong disapproval from unions, largely due to contentious economic reforms such as fuel subsidy removal. The study compares Buhari’s centralized and rigid approach to labor relations with Tinubu’s more mollifying stance, highlighting how both administrations navigated issues of security, economic governance, and public discontent. The paper concludes that successful engagement with unions and careful management of socio-economic reforms are essential for maintaining holistic stability in Nigeria.
Keywords: Governance; social stability; unionism; analysis; administration